P3.223 Antimicrobial susceptibility profile of neisseria gonorrhoeae detected in a public hospital in buenos aires, argentina. (8th July 2017) - Vacchino, M; Tilli, M; Gianecini, R; Almuzara, M; Palombarini, S; Oviedo, C; Sanchez, G; Vulcano, S; Galarza, P
Abstract : Introduction: Gonococcal disease is one of the most common bacterial sexually transmitted infections in the world. The emergence of antimicrobial resistance of Neisseria gonorrhoeae (Ng) to the first-line antimicrobial agents already compromise treatment effectiveness and control of Ng infections. The aim of this study was to know the susceptibility profiles of Ng isolates and clinical features of the patients treated at a public hospital located in the suburbs of Buenos Aires. Methods: We studied 40 isolates of Ng recovered between 2014 and 2015 by the laboratory of bacteriology, from patients attending to the STD office of Eva Perón Hospital. Minimum inhibitory concentrations (MICs) were determined for penicillin (PEN), tetracycline (TET), ciprofloxacin (CIP), azithromycin (AZI), cefixime (CFX) and ceftriaxone (CRO) by agar dilution method (CLSI). B-lactamase was performed by chromogenic cephalosporin method (Nitrocefin). Results: Isolates were recovered from: urethra (36), endocervix (3) and conjunctiva (1). Results of MIC 50 and MIC 90 (μg/ml) were: PEN 0.5 and 4; TET: 1 and 32; CIP: 1 and 4; AZI: 0.25 and 0.5; CFX: 0.016 and 0.03; CRO: 0.008 and 0.016. Isolates with combined resistance to CIP-AZI-PEN, PEN-TET-CIP and CIP-TET-AZI were observed. Cephalosporin resistant Ng isolates was not observed although 2 isolates with decreased susceptibility to CFX (MIC 0.125 µg/ml) were found. The patient medical records were reviewed and no epidemiological relation was found among the patients with harbours strains with simultaneous resistance and clinical features. Patients were treated with CRO 500 mg IM plus AZI 1 g. The post treatment clinical controls were negative. Conclusion: The finding of Ng strains with decreased susceptibility to third generation cephalosporins is a warning signal. In addition to this, the presence of isolates with resistance to different classes of antibiotics, support the need to strength surveillance studies, evaluate treatment failures and improve prevention strategies to control of gonorrhoea in our population.